Garima–An Incentive Based School Assessment System in Odisha: The Case of Koraput District - Mishra, Dr. Latika Kumari (Voices of Teachers and Teacher Educators, 2020)
The success of a school can be determined based on the performances of the students. Generally, we judge the efficiency of a school according to the learning achievement of students. Learning achievement has been considered as the major outcome of quality education. In education system we devise different policies, strategies, and approaches to strengthen the support systems of education with the intention to realize the appropriate learning outcomes. For that we also experiment on many innovations and initiatives at different levels of education to enhance the learning achievements of students. Even we try to implement incentive programs to encourage the teachers and students as a little push to accomplish the goal. Because now a days the major challenge before the school authorities and functionaries is the achievement of appropriate learning outcomes by the students. It is not a problem in one or two schools or districts of the country rather it stands as major challenge throughout the county in India. In order to address this issue the government of Odisha initiated two Learning Enhancement Programmes in 2017 in collaboration with NITI Aayog. After implementation of these programmes assessment procedures were developed to find out the levels of achievements of students under Garima Programme. The programme launched by OSEPA with an objective to improve student outcomes in elementary schools through assessment based on encouragement and incentives. That programme is basically known as Garima- a school certification programme. In this paper an attempt has been made to discuss the significance of Garima programme and the implementation process of this assessment method with special reference to the prospective and challenges associated with Garima while implementing the same in Koraput district of Odisha.